Exosomes in the Pathogenesis and Treatment of Multiple Myeloma in the Context of the Bone Marrow Microenvironment - Chen, Tianzeng; Moscvin, Maria; Bianchi, Giada (Frontiers in Oncology, 2020)
Multiple myeloma (MM), the second most common hematological malignancy, is an incurable cancer of plasma cells. MM cells diffusely involves the bone marrow (BM) and establish a close interaction with the BM niche that in turn supports MM survival, proliferation, dissemination and drug resistance. In spite of remarkable progress in understanding MM biology and developing drugs targeting MM in the context of the BM niche, acquisition of multi-class drug resistance is almost universally inevitable. Exosomes are small, secreted vesicles that have been shown to mediate bidirectional transfer of proteins, lipids, and nucleic acids between BM microenvironment and MM, supporting MM pathogenesis by promoting angiogenesis, osteolysis, and drug resistance. Exosome content has been shown to differ between MM patients and healthy donors and could potentially serve as both cancer biomarker and target for novel therapies. Furthermore, the natural nanostructure and modifiable surface properties of exosomes make them good candidates for drug delivery or novel immunomodulatory therapy. In this review we will discuss the current knowledge regarding exosome’s role in MM pathogenesis and its potential role as a novel biomarker and therapeutic tool in MM.